2013
DOI: 10.12681/mms.318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat and substrate complexity on shallow sublittoral fish assemblages in the Cyclades Archipelago, North-eastern Mediterranean Sea

Abstract: This is the first study to explore fish community structure and its relations to habitat and topographic complexity in the shallow coastal waters of the Cyclades Archipelago, North-eastern Mediterranean Sea. In situ visual surveys were carried out at 233 sampling sites in 26 islands of the Cyclades Archipelago. Fish community parameters and biomass were estimated across seven substrate types: sand, seagrass, vertical walls, boulders, horizontal/subhorizontal continuous rock, rocky substrate with patches of san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
3
25
0
4
Order By: Relevance
“…We focused our research on infralittoral rocky reefs and Posidonia oceanica seagrass meadows (Habitat Types 1170 and 1120 respectively, sensu the EU Habitats Directive 92/43/EEC), as these habitats support the highest fish biomass in the Mediterranean (Harmelin-Vivien et al, 2005;La Mesa et al, 2011;Giakoumi & Kokkoris, 2013) and provide a wide array of marine ecosystem services (Salomidi et al, 2012). To assess the ecological status of these habitats, ad hoc indices and metrics were applied (Orfanidis et al, 2001;Boudouresque et al, 2006;Montefalcone et al, 2007), along the lines of the Habitats (92/43/EEC) and Water Framework (WFD, 2000/60/EE) EU Directives, taking into account the morphological, structural and life-history features of the habitat-forming macrophytes (macroalgae and P. oceanica).…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our research on infralittoral rocky reefs and Posidonia oceanica seagrass meadows (Habitat Types 1170 and 1120 respectively, sensu the EU Habitats Directive 92/43/EEC), as these habitats support the highest fish biomass in the Mediterranean (Harmelin-Vivien et al, 2005;La Mesa et al, 2011;Giakoumi & Kokkoris, 2013) and provide a wide array of marine ecosystem services (Salomidi et al, 2012). To assess the ecological status of these habitats, ad hoc indices and metrics were applied (Orfanidis et al, 2001;Boudouresque et al, 2006;Montefalcone et al, 2007), along the lines of the Habitats (92/43/EEC) and Water Framework (WFD, 2000/60/EE) EU Directives, taking into account the morphological, structural and life-history features of the habitat-forming macrophytes (macroalgae and P. oceanica).…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
“…Where values for a and b were not available, the parameters from congeneric species with similar shape and maximum total length were used. We chose the parameter values that best corresponded (Guidetti & Sala, 2007;Giakoumi & Kokkoris, 2013).…”
Section: A Infralittoral Fish Communitiesmentioning
confidence: 99%
“…Comparative studies have clearly demonstrated substantial differences in fish assemblage composition and structure among these habitats, mainly driven by interspecific differences in the habitat requirements of fishes (Guidetti, 2000;Tunesi et al, 2006;Giakoumi & Kokkoris, 2013). The spatial variability of fish assemblages observed within inshore habitats has been frequently ascribed to differences in depth range (Dufour et al, 1995;Reñones et al, 1997;Letourneur et al, 2003;Tunesi et al, 2006;La Mesa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, considering that the few studies conducted on Mediterranean surf zones have focused only on the macro-and supra-benthic communities (León & Corrales, 1995;Munilla et al, 1998;San Vicente & Munilla, 2000;Deidun & Schembri, 2006;Esposito et al, 2011;Esposito, 2013) or on fish assemblages of Adriatic or north-eastern Mediterranean Sea (Lipej et al, 2003;Giakoumi & Kokkoris, 2013) the specific objectives of this paper were: 1) to investigate, for the first time, the taxonomic composition of a fish assemblage in a surf zone of the Tyrrhenian Sea; 2) to assess the assemblage structure, with the aim of providing information on the functional aspects of this shallow water habitat for the ichthyofauna.…”
Section: Introductionmentioning
confidence: 99%